2021
DOI: 10.1093/alcalc/agab030
|View full text |Cite
|
Sign up to set email alerts
|

Linking Big Five Personality Domains and Facets to Alcohol (Mis)Use: A Systematic Review and Meta-Analysis

Abstract: Aims The goal of this investigation was to synthesize (un)published studies linking Big Five personality domains and facets to a range of alcohol use outcomes. Meta-analyses were conducted to quantify the unique associations between alcohol use outcomes and each Big Five personality domains over and above other domains. Within each domain, meta-analyses also were conducted to examine the unique contribution of each personality facet in predicting alcohol use outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
32
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 51 publications
9
32
2
Order By: Relevance
“…Future work would benefit from using measures of personality that are able to capture these granular elements of personality. This is important in light of evidence that other forms of externalizing psychopathology (e.g., alcohol use) have meaningful personality predictors across multiple domains (Lui et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Future work would benefit from using measures of personality that are able to capture these granular elements of personality. This is important in light of evidence that other forms of externalizing psychopathology (e.g., alcohol use) have meaningful personality predictors across multiple domains (Lui et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…addiction diagnostic guidelines), may, in fact, be linked with and reflect a distinctive underlying personality and its development. Personality traits have been conceptualized not only to constitute genetic phenotypes disposing for alcohol use ( 14 ), but also driving forces behind the motivations to engage in drinking behaviors as well as behind the very drinking paradigms ( 15 ). Hence, individually targeted interventions have proven useful in prevention of AUDs and other addictions ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…In two different studies, Zilberman et al ( 29 , 30 ) found all addiction populations to manifest greater impulsivity and neuroticism relative to controls, while individuals with AUDs to also score lower on extraversion, agreeableness, and openness to experience. Next to low agreeableness (particularly the facets compliance and straightforwardness), meta-analytic evidence seems to implicate also lower conscientiousness (mostly the facets deliberation and dutifulness) as a likely predictor of pathological alcohol consumption, with certain facets of extraversion (i.e., excitement seeking) and neuroticism (i.e., impulsiveness and angry hostility) considered accountable for affecting drinking behaviors and alcohol-related problems ( 15 ). What this brief review of evidence therefore suggests is that rather than factors per se , it may be certain profiles of characteristics that seem to be related to AUDs.…”
Section: Introductionmentioning
confidence: 99%
“…Considering this, available meta-analytic evidence suggests higher alcohol consumption in persons with low conscientiousness (responsible for self-control, flexibility, and adherence to social norms), low agreeableness (cooperativeness, kindness, and trust towards others), and high neuroticism (little emotional stability, proneness to anxiety, and sensitivity to negative emotions) [ 10 ]. Next to low agreeableness (compliance and straightforwardness in particular), low conscientiousness (mostly deliberation and dutifulness) and high neuroticism (i.e., impulsiveness and angry hostility), another meta-analysis seems to also implicate certain facets of extraversion (i.e., excitement-seeking) as likely predictors of pathological alcohol use [ 11 ], thus highlighting the associations between the two notions. Regarding facets related to alcohol abuse, past or present diagnoses thereof were found to be linked to low scores on “trust, achievement striving, self-discipline, and dutifulness” and high scores on “impulsiveness, vulnerability, and excitement-seeking” [ 12 ].…”
Section: Introductionmentioning
confidence: 99%